KARAKALPAK FOLK SONGS ARE A SPECIAL KIND OF FOLKLORE - Allambergenov, K.; Kanaatov, E. (FAN va JAMIYAT, 2020)
The article provides information on the history of the Karakalpak people in the period of the emergence of the Saka-Massaget and Turkic peoples, and for the first time the historical poems recorded among the Taulibay Karakalpaks were submitted for scientific discussion. There are also spoken about the genre, content, historical value and character of the historical songs of the Karakalpak people from the XIII century to the 20s of the XX century. The article briefly discusses the classification of historical songs and comments on the role of tropes in increasing the effectiveness of historical songs.